Mannheimia haemolytica in Feedlot Cattle: Prevalence of Recovery and Associations with Antimicrobial Use, Resistance, and Health Outcomes. (March 2015) - Noyes, N.R.; Benedict, K.M.; Gow, S.P.; Booker, C.W.; Hannon, S.J.; McAllister, T.A.; Morley, P.S.
Abstract : Background: Mannheimia haemolytica is an important etiological agent in bovine respiratory disease. Objectives: Explore risk factors for recovery of susceptible and resistant M. haemolytica in feedlot cattle and explore associations with health outcomes. Animals: Cattle (n = 5, 498) from 4 feedlots sampled at arrival and later in feeding period. Methods: Susceptibility of M. haemolytica isolates tested for 21 antimicrobials. Records of antimicrobial use and health events analyzed using multivariable regression. Results: M. haemolytica recovered from 29% of cattle (1, 596/5, 498), 13.1% at arrival (95% CI, 12.3–14.1%), and 19.8% at second sampling (95% CI, 18.7–20.9%). Nearly half of study cattle received antimicrobial drugs (AMDs) parenterally, mostly as metaphylactic treatment at arrival. Individual parenteral AMD exposures were associated with decreased recovery of M. haemolytica (OR, 0.2; 95% CI, 0.02–1.2), whereas exposure in penmates was associated with increased recovery (OR, 1.5; 95% CI, 1.05–2.2). Most isolates were pan‐susceptible (87.8%; 95% CI, 87.0–89.4%). AMD exposures were not associated with resistance to any single drug. Multiply‐resistant isolates were rare (5.9%; 95% CI, 5.1–6.9%), but AMD exposures in pen mates were associated with increased odds of recovering multiply‐resistant M. haemolytica (OR, 23.9; 95% CI, 8.4–68.3). Cattle positive for M. haemolytica on arrival were more likely to become ill within 10 days (OR, 1.7; 95% CI, 1.1–2.4). Conclusions and Clinical Importance: Resistance generally was rare in M. haemolytica . Antimicrobial drug exposures in penmates increased the risk of isolating susceptible and multiply‐resistant M. haemolytica, a finding that could be explained by contagious spread.